2009
DOI: 10.1007/s12264-009-0918-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher cortical modulation of pain perception in the human brain: Psychological determinant

Abstract: Pain perception and its genesis in the human brain have been reviewed recently. In the current article, the reports on pain modulation in the human brain were reviewed from higher cortical regulation, i.e. top-down effect, particularly studied in psychological determinants. Pain modulation can be examined by gene therapy, physical modulation, pharmacological modulation, psychological modulation, and pathophysiological modulation. In psychological modulation, this article examined (a) willed determination, (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
3
0
2
Order By: Relevance
“…Moreover, the neural activity pattern that emerges from these studies is compliant with the one observed in other paradigms that studied the impact of various forms of suggestion or induced beliefs on perceived pain, such as anticipation/placebo (Zubieta & Stohler, 2009) or hypnotic suggestion (Del Casale et al, 2015). This indicates that changing the meaning of potentially threatening or unpleasant stimuli, which is a driving force of reappraisal, may be a more universal mechanism that underlies all forms of higher-level cognitive pain modulation (Barber, 1957;Chen, 2009;van der Meulen, Kamping, & Anton, 2017;Wiech et al, 2008). However, to the best of our knowledge, none of the previous studies analyzed the exact time sequence of the observed neural modulations, which would require a much more accurate temporal resolution than the one offered by the functional resonance imaging (fMRI) that was predominantly used in these studies.…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, the neural activity pattern that emerges from these studies is compliant with the one observed in other paradigms that studied the impact of various forms of suggestion or induced beliefs on perceived pain, such as anticipation/placebo (Zubieta & Stohler, 2009) or hypnotic suggestion (Del Casale et al, 2015). This indicates that changing the meaning of potentially threatening or unpleasant stimuli, which is a driving force of reappraisal, may be a more universal mechanism that underlies all forms of higher-level cognitive pain modulation (Barber, 1957;Chen, 2009;van der Meulen, Kamping, & Anton, 2017;Wiech et al, 2008). However, to the best of our knowledge, none of the previous studies analyzed the exact time sequence of the observed neural modulations, which would require a much more accurate temporal resolution than the one offered by the functional resonance imaging (fMRI) that was predominantly used in these studies.…”
Section: Introductionsupporting
confidence: 70%
“…However, inconsistency in spectral features of BWM or CBT was found compared with previous literature on pain mechanisms, which revealed that a decrease in ‘slow’ wave activity (mainly theta and alpha bands) and an increase in ‘fast’ wave activity (beta and gamma bands) are associated with pain perception (Chen, ; Bromm and Lorenz, ; Huber et al , ; Shao et al , ). Furthermore, the reinforcement of theta and alpha activity and the suppression of beta (or gamma) activity have been reported to be associated with the analgesic effects of NF, meditation and hypnosis (Chen, ; Jensen et al , , ). In our study, different from the CBT group with a decreased overall power spectrum, BWM showed increased theta activity in extensive brain regions (frontal, parietal and occipital) and occipital alpha activity, whilst the changes in beta activity were not remarkable (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…A Hipnologia é hoje um campo de pesquisa promissor, que pode trazer respostas a questões ainda persistentes na Ciência do Comportamento e Neurociências [51][52][53][54] . Estudos recentes sobre mecanismos envolvidos nos processos cognitivo, afetivo e motor têm incluído a hipnose em seus desenhos experimentais, associando-a a técnicas de neuroimagem funcional 39,55 e EEG [56][57][58] . No presente trabalho, uma revisão de literatura sobre as mudanças no EEG que acompanham a "hipnose animal" e a hipnose humana é apresentada.…”
Section: Revisão De Literaturaunclassified